Predictive Factors of Literacy Achievement in Young Gifted Children in Rural Schools. Issue 3 (August 2019) - El-Abd, Maria; Callahan, Carolyn; Azano, Amy
The present study investigated predictive factors of literacy achievement in third-grade students identified as gifted in rural schools. The sample consisted of 180 identified students in a total of eight districts, three of which were randomly assigned to the treatment condition and five of which were randomly assigned to the control condition. Students in the treatment condition received instruction with a place-based folklore unit of the Challenge Leading to Engagement, Achievement, and Results (CLEAR) curriculum, a language arts based curriculum designed to challenge gifted learners, in addition to an intervention promoting an incremental mind-set. Results of the present study indicated that prior achievement, mind-set, and gender were all statistically and practically significant predictors of literacy achievement for students identified as gifted in rural areas. A stronger incremental mind-set was associated with lower literacy achievement scores. Practical implications and recommendations, as well as limitations and directions for further research, were discussed.